The term structure of interest rates: Estimation and interpretation - Juha Seppälä; Petri Viertiö (Bank of Finland, 1996)
This document reports the currently used term structure estimation method at the Bank of Finland and discusses interpretation of the results it generates.We start by introducing two widely used term structure estimation methods: the Cubic Spline Function method and the Nelson-Siegel approach.We compare their results, paying special attention to the smoothness of forward interest rates and distribution of pricing errors.Next, we introduce the Bank of Finland's method, commenting on its strenghts and weaknesses. Finally, we discuss interpretation of the term structure of interest rates with emphasis on the inflation expectations and the role of the time-varying risk premia.
URN:NBN:fi:bof-20140807632
Keywords: 330; term structure of interest rates; cubic splines; Nelson-Siegel; forward interest rates; relative value; inflation expectations; time-varying risk premia